2017
DOI: 10.1101/142927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain xQTL map: Integrating the genetic architecture of the human brain transcriptome and epigenome

Abstract: We perform quantitative trait locus (xQTL) analyses on a multi-omic dataset, comprising RNA sequence, DNA methylation, and histone acetylation ChIP sequence data from the dorsolateral prefrontal cortex of 411 older adult individuals. We identify SNPs that are significantly associated with gene expression, DNA methylation, and histone modification levels. Many SNPs influence more than one type of molecular feature, and epigenetic features are shown to mediate eQTLs in a number of (9%) such loci. We illustrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…More interestingly, however, we found that genetic variants that affect RNA splicing were most enriched (14× fold-enrichment) in variants associated to PD at p-value < 10 −5 . This observation is consistent across two different DLFPC datasets 18,21 , and motivated us to explore the hypothesis that PD-associated variants may affect RNA expression or splicing of nearby genes in myeloid cells and in cells from the CNS.…”
Section: Heritability Enrichment Of Expressed Genes Identifies Pd-relmentioning
confidence: 52%
See 3 more Smart Citations
“…More interestingly, however, we found that genetic variants that affect RNA splicing were most enriched (14× fold-enrichment) in variants associated to PD at p-value < 10 −5 . This observation is consistent across two different DLFPC datasets 18,21 , and motivated us to explore the hypothesis that PD-associated variants may affect RNA expression or splicing of nearby genes in myeloid cells and in cells from the CNS.…”
Section: Heritability Enrichment Of Expressed Genes Identifies Pd-relmentioning
confidence: 52%
“…To further support the results from our splicing TWAS analysis, we performed additional analyses to replicate our TWAS in independent transcriptome 21 and GWAS datasets (23andMe cohort 27 ). We first assessed whether the DLPFC TWAS results could be replicated in an independent transcriptomic reference panel by performing TWAS using DLPFC RNA-seq data from ROS/MAP 22 .…”
Section: Dlpfc Sqtls (Supplementarymentioning
confidence: 85%
See 2 more Smart Citations
“…A summary description of all the data sets can be found in Supplementary Table 1, Supplementary Table 3, and Supplementary Table 6. All the samples were of European descent and the summary data available to us were derived from individual-level data that passed stringent quantify control (QC) 9,11,20,22,[33][34][35]46 . The SNPs in all eQTL/mQTL data sets were from imputation of the genotyped data to the 1000 Genomes Project (1KGP) reference panels 47 , and only the common SNPs (MAF > 0.01) were included in analyses.…”
Section: Summary Data Of Cis-eqtl Cis-mqtl and Gwasmentioning
confidence: 99%